Pelaksanaan Gadai Emas Dengan Sistem Syariah Di Bank Mandiri Syariah Cabang Kisaran - Jhon Amri S Pasaribu; Elvi Zahara Lubis; Muhammad Yusrizal Adi Syaputra (JUNCTO: Jurnal Ilmiah Hukum, 2020)
Profit sharing system in Islamic banks is one of the uses of sharia principles because interest is contrary to Islamic law. This type of research used in this study is normative legal research and the nature of the research is analytical descriptive. Sources of data used in this study are secondary data and primary data. The results of the study are the implementation of a gold pawning system with sharia at Bank Mandiri Syariah Kisaran Branch Office using 3 (three) contracts on gold-backed qaradh products, rahn contracts for gold binding and ijarah contracts for binding utilization of gold storage and maintenance services as collateral for loan funds. The implementation of the gold pawning is in accordance with the rules of Islamic law and sharia principles regarding gold rahn. The obstacles that arise in the implementation of the gold pawning with the sharia system that is not understanding the mechanism of rahn contract, customers who are not disciplined in paying installments so that when the gold is mortgaged auctioned auctioned by the bank and collateral carried by the customer does not comply with the specified specifications by the bank.